Makna Kesederhanaan dan Kekudusan Berdasarkan 1 Timotius 2:9 - Lidia Veriani (Views : Jurnal Teologi dan Biblika, 2025)
This study analyzes the theological meaning of simplicity and holiness based on 1 Timothy 2:9 through a contextual hermeneutical approach and lexical analysis. This verse instructs women to dress “modestly and modestly, not with braided hair or gold or pearls or expensive clothing,” in the context of first-century Ephesus influenced by the cult of Artemis and the “new Roman woman,” where the opulence of ostentatious appearance interferes with Christian worship. The lexical analysis of katastolē (modest clothing) and kosmios (modest/orderly) shows simplicity as an anti-materialist rejection of worldly vanity, prioritizing spiritual focus over externals. Holiness is related to aidos (godly humility) and sōphrosynē (self-control/moderation), reflecting a transformed heart, spiritual identity, and socio-spiritual harmony. Contemporary implications transcend gender/culture, encouraging all believers to counter consumerism/social media with humility, resource stewardship, and Christ-honoring witness through inner integrity.